Brazilian Curcuma longa L. attenuates comorbidities by modulating adipose tissue dysfunction in obese rats - Lo, Angelo Thompson Colombo [UNESP] (2018)
Background: Adipose tissue dysfunction is a condition characterized by inflammation and oxidative stress able to lead metabolic disorders. Curcuma longa L. (Cl) is a rhizome commonly used in Indian culinary which presents anti-inflammatory and antioxidant compounds. The aim of this study was to evaluate the effect of in natura Curcuma longa L. on adipose tissue dysfunction and comorbidities in obese rats. Methods: Male Wistar rats (8 weeks old, n = 16) received standard chow + fructose in drinking water (30%) ad libitum for 16 weeks. After this period, animals were randomly divided to receive placebo treatment (fructose, n = 8) or Curcuma longa L. treatment (fructose + Cl, n = 8) for more 8 weeks, totalizing 24 weeks of experiment. Curcuma longa L. was mixed in water and gave to the animals by gavage in a dose of 80 mg/kg of body weight. Body composition, systolic blood pressure, metabolic, hormonal, inflammatory, and oxidative stress analysis were performed in plasma and adipose tissue. Results: Curcuma longa L. reduced adiposity index and adipocyte hypertrophy, improved insulin resistance and systolic blood pressure, and reduced inflammation and oxidative stress in adipose tissue. Conclusion: Curcuma longa L. in natura is able to modulate adipose tissue dysfunction, avoiding the development of comorbidities. It can be considered a phytochemical treatment strategy against obesity-related chronic diseases.